Low depression literacy exacerbates the development and progression of depressive mood in Chinese adult social media users during COVID-19: A 3-month observational online questionnaire-based study with multiple cross-sectional analyses - Shan, Dan; Li, Shaoyang; Xu, Ruichen; Huang, Jingtao; Wang, Yi; Zheng, Yuandian; Huang, Shanshan; Song, Yuming; Han, Junchu; Suto, Sayaka; Dai, Zhihao (Frontiers in Public Health, 2023)
Background The main purpose of this study was to explore the relationship between depression literacy (D-Lit) and the development and progression of depressive mood. Methods This longitudinal study with multiple cross-sectional analyses used data from nationwide online questionnaire administered via Wen Juan Xing survey platform. Eligible participants were 18 years of age or older and had subjectively experienced mild depressive mood at the time of their initial enrollment in the study. The follow-up time was three months. Spearman's rank correlation test was used to analyze the predictive role of D-Lit on the later development of depressive mood. Results We included 488 individuals with mild depressive mood. In terms of Spearman's correlations, no statistically significant correlation between D-Lit and Zung self-rating depression scale (SDS) at baseline was observed (adjusted rho = 0.001, p = 0.974). However, after 1 month (adjusted rho = -0.449, p < 0.001) and after 3 months (adjusted rho = -0.759, p < 0.001), D-Lit was significantly and negatively correlated with SDS. Limitations The targeted subjects were limited to Chinese adults; meanwhile, China's current management policies for COVID-19 differ from most other countries, limiting the generalizability of this study. Conclusions Despite the limitations, our study provided novel evidence supporting that low depression literacy may be associated with exacerbated development and progression of depressive mood, which, if not appropriately and promptly controlled, may ultimately lead to depression. In the future, we encourage further research to explore effective and efficient ways to enhance public depression literacy.